Modeling metabolizable energy utilization in broiler breeder pullets - Sakomura, N. K. [UNESP]; Silva, R. [UNESP]; Couto, H. P.; Coon, C.; Pacheco, C. R. (Elsevier, 2003)
The objective of this study was to determine models for ME requirements for broiler breeder pullets using the factorial method. The influence of the temperature on maintenance ME requirements was determined by experiments conducted in three environmental rooms with temperature kept constant at 15, 22, and 30°C, using the comparative slaughter technique. The energy requirements for weight gain were determined based on the body energy content and efficiency of energy utilization for weight gain. Two ME requirement models for each age were developed using the coefficients for maintenance and weight gain. The models for 3 to 8 wk were ME = W 0.75 (186.52 - 1.94T) + 2.47WG, and ME = W 0.75 (174 - 1.88T) + 2.83WG; for 9 to 14 wk, ME = W 0.75 (186.52 - 1.94T) + 2.69WG, and ME = W 0.75 (174 - 1.88T) + 2.50WG; and 15 to 20 wk, ME = W 0.75 (186.52 - 1.94T) + 2.76WG, and ME = W 0.75 (174 - 1.88T) + 3.24WG. In these equations, W is BW (kg), T is temperature (°C), and WG is daily weight gain (g). These models were compared to the breeder's recommendations in a feeding trial from 5 to 20 wk of age. Models 1 and 2 provided energy intakes that promoted BW smaller than the breeder's recommendation. However, all breeder pullets had weights above the standard recommendation. Model 2 gave the smallest ME intake and BW close to the standard recommendation and provided the best prediction of ME requirements.
Keywords: Broiler breeder pullet; Comparative slaughter technique; Energy model; Factorial method; Metabolizable energy requirement